Selectively permeable interlayer
By using a selective permeability interlayer in lithium-sulfur batteries, the structural problems caused by changes in insulation and volume during charging and discharging of the battery are solved, and by hindering the shuttle of polysulfides, irreversible capacity loss is reduced, and higher cycling stability and energy density are achieved.
Patent Information
- Application Number
- CN202380052958.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-27
- Publication Date
- 2025-03-18
AI Technical Summary
The main technical challenges faced by lithium-sulfur batteries during charging and discharging include the insulating properties of solid sulfur, structural damage caused by volume changes, and irreversible capacity losses caused by the ‘shuttle effect’.
A selective permeability interlayer is adopted, which consists of elastic polyelectrolyte liquid and two-dimensional conductive material. By controlling the proportion and composition of the material, the rapid transport of lithium ions is achieved while hindering the shuttle of polysulfides.
This interlayer effectively reduces the accumulation of polysulfides on the surface of the interlayer, promotes the conduction of lithium ions, reduces irreversible capacity loss, and improves the cycle stability and energy density of lithium-sulfur batteries.
Smart Images

Figure BDA0005235681680000131 
Figure BDA0005235681680000152 
Figure BDA0005235681680000153
Abstract
Description
Technical Field
[0001] The present disclosure relates to a permselective interlayer for lithium-sulfur batteries, a method for preparing the interlayer, a separator coated with the interlayer, and a lithium-sulfur battery incorporating the separator. Background Art
[0002] Lithium-sulfur batteries have attracted increasing attention from academia and industry because their theoretical specific energy density is much higher than that of lithium-ion batteries.
[0003] However, lithium-sulfur batteries face technical challenges that have so far limited their widespread adoption and commercialization. These challenges include the insulating properties of solid sulfur and large volume changes during charge and discharge, which can cause structural damage to the sulfur cathode. In addition, during the discharge process, intermediate lithium polysulfides (LiPS) are at least partially dissolved in the electrolyte and can therefore diffuse from the cathode to the anode and be further reduced by lithium metal to form a non-conductive solid. This phenomenon is also known as the Li-S "shuttling effect".
[0004] These non-conductive solids may accumulate on the surface of the lithium metal anode and cannot be easily transferred from the solid phase back to the liquid phase, which can lead to continuous cathode active material loss and lithium anode passivation, resulting in irreversible capacity loss.
[0005] To date, several strategies have been used to try to counter the shuttling effect. One strategy involves providing a physical barrier or interlayer in an attempt to suppress the shuttling effect. However, in addition to providing such suppression, the interlayer should at least maintain the Li + Rapid transport and strong adhesion to the porous membrane substrate (typically a hydrophobic polyolefin).
[0006] There remains a need for improved interlayers for lithium-sulfur batteries that address at least some of the aforementioned problems.
[0007] The reference to any prior art in this specification does not constitute an acknowledgement or implication that this prior art forms part of the common general knowledge in any jurisdiction, nor does it mean that this prior art can be reasonably understood by a person skilled in the art, regarded as related to and / or combined with other prior art. Summary of the invention
[0008] In one aspect, the present disclosure provides a permselective interlayer for a lithium-sulfur battery, the permselective interlayer comprising:
[0009] a) one or more elastomeric polyelectrolyte liquids; and
[0010] b) One or more two-dimensional conducting materials.
[0011] In an embodiment, the selectively permeable interlayer comprises:
[0012] a) from about 15 wt.% to about 45 wt.% of one or more elastomeric polyelectrolyte liquids; and
[0013] b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials;
[0014] The wt. % is based on the total weight of the permselective interlayer.
[0015] In an embodiment, the selectively permeable interlayer comprises:
[0016] a) from about 20 wt.% to about 40 wt.% of one or more elastomeric polyelectrolyte liquids; and
[0017] b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials;
[0018] The wt. % is based on the total weight of the permselective interlayer.
[0019] In an embodiment, the weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is about 1:1.5 to about 1:3.5.
[0020] In an embodiment, the elastic polyelectrolyte liquid comprises a mixture of:
[0021] a) from about 40 wt.% to about 80 wt.% of one or more polyphenols;
[0022] b) from about 5 wt.% to about 40 wt.% of one or more cationic polymers; and
[0023] c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins;
[0024] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0025] In an embodiment, the elastic polyelectrolyte liquid comprises a mixture of:
[0026] a) from about 50 wt.% to about 80 wt.% of one or more polyphenols;
[0027] b) from about 15 wt.% to about 40 wt.% of one or more cationic polymers; and
[0028] c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins;
[0029] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0030] In an embodiment, the elastic polyelectrolyte liquid comprises a mixture of:
[0031] a) from about 50 wt.% to about 70 wt.% of one or more polyphenols;
[0032] b) from about 15 wt.% to about 35 wt.% of one or more cationic polymers; and
[0033] c) from about 10 wt.% to about 30 wt.% of one or more ion transport enhancing proteins;
[0034] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0035] In embodiments, the one or more polyphenols have a molecular weight of about 100 Daltons to about 20,000 Daltons or about 200 Daltons to about 20,000 Daltons.
[0036] In embodiments, the one or more polyphenols comprise one or more of tannic acid, caffeic acid, gallic acid, ellagitannin, gallotannin, tannic acid, proanthocyanidin, and curcumin.
[0037] In embodiments, the one or more cationic polymers comprise amine functional groups.
[0038] In embodiments, the one or more cationic polymers comprise one or more of: polyethyleneimine, poly(allylamine) hydrochloride, poly(lysine), poly(DADMAC), and chitosan.
[0039] In embodiments, the one or more ion transport enhancing proteins comprise one or more of the following: bovine serum albumin, lysosome, ovalbumin, and valinomycin.
[0040] In an embodiment, the one or more two-dimensional conductive materials include one or more of the following: reduced graphene oxide, transition metal dichalcogenides, metal organic frameworks, phosphorene, and nitrides.
[0041] The transition metal dichalcogenide may include MX 2 wherein M is Mo, W or V, and X is S, Se or Te.
[0042] In an embodiment, the selectively perminterlayer comprises both hydrophilic and hydrophobic domains.
[0043] In an embodiment, the zero shear viscosity of the permselective interlayer measured between 20°C and 25°C is less than 500 Pa.s.
[0044] In another aspect, the present disclosure provides a separator for a lithium-sulfur battery, the separator comprising a porous substrate coated with a selectively permeable interlayer according to any one of the embodiments disclosed herein.
[0045] In an embodiment, the porous substrate comprises one or more polyolefins.
[0046] In embodiments, the selectively perminterlayer on the membrane has a thickness of about 100 nm to about 400 nm, or about 150 nm to about 350 nm, or about 200 nm to about 300 nm.
[0047] In embodiments, the permselective interlayer coating comprises pores of a size large enough to allow transport of lithium ions through the separator.
[0048] In an embodiment, the selectively permeable interlayer coating comprises pores of a size small enough to hinder the transport of polysulfide species through the membrane. The selectively permeable interlayer coating may hinder the transport of more than 90% of polysulfide species, or more than 95%, or up to 99% or more of polysulfide species through the membrane.
[0049] In embodiments, the permselective interlayer coating mitigates accumulation of polysulfide species on a surface of the permselective interlayer coating.
[0050] In another aspect, the present disclosure provides a lithium-sulfur battery comprising a lithium anode, a sulfur cathode, a separator coated with a selectively permeable interlayer according to any one of the embodiments disclosed herein, and an electrolyte disposed between the anode and the cathode.
[0051] In an embodiment, the permselective interlayer coating mitigates accumulation of polysulfide species on a surface of the permselective interlayer coating during charging or discharging of the battery.
[0052] In an embodiment, the selectively permeable interlayer coating oxidizes or reduces polysulfide species during charging or discharging of the battery.
[0053] In embodiments, the permselective interlayer coating facilitates transport of lithium ions across the separator during charging or discharging of the battery.
[0054] In embodiments, the permselective interlayer coating blocks transport of polysulfide species across the separator during charging or discharging of the battery.
[0055] In embodiments, the selectively permeable interlayer coating blocks transport of more than 90% of polysulfide species, or more than 95%, or up to 99% or more of polysulfide species across the membrane.
[0056] In an embodiment, the electrolyte volume to capacity ratio of the lithium-sulfur battery is less than or equal to 5 μL mAh-1.
[0057] In another aspect, the present disclosure provides a method of producing a selectively permeable interlayer according to any one of the embodiments disclosed herein, the method comprising combining one or more elastic polyelectrolyte liquids with one or more two-dimensional conductive materials.
[0058] When the two-dimensional conductive material is graphene oxide, the combination of one or more elastic polyelectrolyte liquids and graphene oxide is heated to a temperature greater than 60° C. to reduce at least some of the graphene oxide.
[0059] In the method, a weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is from about 1:1.5 to about 1:3.5.
[0060] In another aspect, the present disclosure provides a method of producing a membrane according to any one of the embodiments disclosed herein, the method comprising coating a porous substrate with a selectively permeable interlayer according to any one of the embodiments disclosed herein.
[0061] In another aspect, the present disclosure provides an elastic polyelectrolyte solution comprising a mixture of one or more polyphenols, one or more cationic polymers, and one or more ion transport facilitating proteins.
[0062] In another aspect, the present disclosure provides a method for preparing an elastic polyelectrolyte solution according to any one of the embodiments disclosed herein:
[0063] a) combining one or more polyphenols with one or more cationic polymers; and
[0064] b) adding one or more ion transport enhancing proteins,
[0065] Wherein a) and b) are carried out under acidic conditions.
[0066] Advantages of the currently disclosed selectively permeable interlayers include one or more of the following:
[0067] ●Selective permeability transport of lithium ions;
[0068] ●Hinder or eliminate polysulfide transport;
[0069] ●Reactivation and recovery of polysulfides;
[0070] ●Strong adhesion to the diaphragm substrate.
[0071] Unless explicitly stated otherwise, any embodiment herein should be considered applicable to any other embodiment mutatis mutandis.
[0072] The scope of the present disclosure is not to be limited by the specific embodiments described herein, which are provided for illustrative purposes only. As described herein, functionally equivalent products, compositions and methods are clearly within the scope of the present disclosure.
[0073] Further aspects of the disclosure and further embodiments of the aspects described in the preceding paragraphs will become apparent from the following description, which is given by way of example and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 Shown are: A) a phase diagram showing the preferred compositional region for the formation of an elastomeric polyelectrolyte liquid (EPL).
[0075] Figure 2 Shown are: E) zero shear viscosity; F) polarization microscopy image of EPL-rGO showing liquid domain crystallinity.
[0076] Figure 3 The relationship between the reduction time, conductivity and coatability of different EPL:GO compositions was pointed out.
[0077] Figure 4 Shown are: A) schematic diagram showing the narrow and wide channels of EPL-rGO; B) XRD pattern and C) positron lifetime trajectory of EPL-rGO.
[0078] Figure 5 It shows: A) in Li 2 S 4 Optical images of diffused battery cells with different permselective interlayers; A) Summary of LiPS repulsion and interlayer spacing characteristics of different permselective materials; C) Different interlayers in Li 2 S 6 Long-term stability testing with solvents and salts at 2 mM solutions lasted for 48 hours.
[0079] Figure 6 Plots of interlayer thickness versus ionic conductivity and percent lithium polysulfide rejection are shown.
[0080] Figure 7 Shown: A) across 3.2 mg cm -2A) Comparison of permselective interlayers of button cell cells assembled with higher sulfur loading; B) CV comparison; C) Nyquist plot of the cell; D) charge / discharge spectra; and E) cycling data at higher rates; and F) higher sulfur loading.
[0081] Figure 8 Shown are: A) pouch battery cell cycling performance; B) double-sided cathode pouch battery cell; C) charge-discharge spectrum of pouch battery cell; D) Nyquist plot.
[0082] Fig. 9 Shown: A) Schematic diagram depicting ionic conductivity and Li + Schematic diagram of the cell setup for transfer number characterization; B) Summary of results obtained by imaging the underlying electrolyte contact angle; C) Proposed Li + Mechanism of transport across the EPL-rGO interlayer; D) Activation energy obtained from the temperature-dependent slope of the resistance.
[0083] Fig.10 Shown are: A) a cathode electrolyte half-cell using EPL-rGO as an electrode setup in the absence of sulfur; B) the electrochemical activity of the EPL-rGO separator is demonstrated by the CV curve - the presence of significant peaks indicates that EPL-rGO is able to catalyze the electrochemical reactions of different LiPS species.
[0084] Fig.11 The CV curve of a symmetric cell is shown, which shows that there is a current response between -0.8V and 0.8V upon polarization.
[0085] Fig.12 Symmetrical CV curves are shown, comparing the EPL-rGO material with other commonly used redox mediators and electrocatalysts.
[0086] Fig.13 shows a span of 3 mg cm -2 Comparison of the sulfur loading and permselective interlayers of button cell cells assembled with different combinations of polyphenols, cationic polymers, and ion transport-enhancing proteins. DETAILED DESCRIPTION
[0087] It should be understood that the disclosure described and defined in this specification extends to all alternative combinations of two or more of the individual features mentioned or evident in the text or drawings. All these different combinations constitute various alternative aspects of the disclosure.
[0088] definition
[0089] For the purpose of interpreting this specification, terms used in the singular form will also include the plural form, and vice versa.
[0090] As used herein, the term "comprise" and variations of the term such as "comprising," "comprises," and "comprised" are not intended to exclude additional additives, components, integers or steps, unless the context requires otherwise.
[0091] As used herein, "about" when referring to a measurable value such as an amount, duration, etc., is intended to encompass variations of ±20% or ±10%, in some instances ±5%, in some instances ±1%, and in some instances ±0.1% relative to the specified value, as such variations are suitable for performing the disclosed methods.
[0092] As used herein, the term "polyphenol" refers to a chemical compound having more than one hydroxyl group on an aromatic ring. Thus, the term includes chemical compounds such as phenolic acids having more than one hydroxyl group on an aromatic ring.
[0093] Range: Throughout this disclosure, various aspects of the invention may be presented in a range format. It should be understood that description in a range format is merely for convenience and brevity, and should not be construed as a rigid limitation on the scope of the invention. Therefore, the description of a range should be considered to have all possible subranges specifically disclosed as well as individual numerical values within the range. For example, a description of a range such as 1 to 6 should be considered to have specific disclosed subranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., as well as individual numbers within the range, such as 1, 2, 2, 7, 3, 4, 5, 5.3, and 6. This applies regardless of the width of the range.
[0094] The present disclosure relates to a novel permselective interlayer for lithium-sulfur batteries. The interlayer promotes the transport of lithium ions but eliminates the transport of polysulfide anions. In addition, the interlayer advantageously reduces the surface accumulation of polysulfide species.
[0095] Selective permeability interlayer
[0096] The present disclosure provides a selective permeability interlayer for a lithium-sulfur battery, the selective permeability interlayer comprising:
[0097] a) one or more elastomeric polyelectrolyte liquids; and
[0098] b) One or more two-dimensional conducting materials.
[0099] In an embodiment, the selectively permeable interlayer comprises:
[0100] a) from about 15 wt.% to about 45 wt.% of one or more elastomeric polyelectrolyte liquids; and
[0101] b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials;
[0102] The wt. % is based on the total weight of the permselective interlayer.
[0103] In an embodiment, the selectively permeable interlayer comprises:
[0104] a) from about 20 wt.% to about 40 wt.% of one or more elastomeric polyelectrolyte liquids; and
[0105] b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials;
[0106] The wt. % is based on the total weight of the permselective interlayer.
[0107] The amount of the one or more elastic polyelectrolyte liquids in the permselective interlayer may be about 15 wt.% to about 45 wt.%, or about 20 wt.% to about 45 wt.%, or about 25 wt.% to about 45 wt.%, or about 30 wt.% to about 45 wt.%.
[0108] The amount of the one or more two-dimensional conductive materials in the selectively perminterlayer may be about 40 wt.% to about 80 wt.%, or about 45 wt.% to about 80 wt.%, or about 50 wt.% to about 80 wt.%, or about 55 wt.% to about 80 wt.%, or about 60 wt.% to about 80 wt.%, or about 65 wt.% to about 80 wt.%, or about 70 wt.% to about 80 wt.%, or about 75 wt.% to about 80 wt.%.
[0109] In an embodiment, the weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is about 1:1.5 to about 1:3.5.
[0110] Elastic polyelectrolyte liquid
[0111] The one or more elastomeric polyelectrolyte liquids may comprise a mixture of:
[0112] a) from about 40 wt.% to about 80 wt.% of one or more polyphenols;
[0113] b) from about 5 wt.% to about 40 wt.% of one or more cationic polymers; and
[0114] c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins;
[0115] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0116] The one or more elastomeric polyelectrolyte liquids may comprise a mixture of:
[0117] a) from about 50 wt.% to about 80 wt.% of one or more polyphenols;
[0118] b) from about 15 wt.% to about 40 wt.% of one or more cationic polymers; and
[0119] c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins;
[0120] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0121] The one or more elastomeric polyelectrolyte liquids may comprise a mixture of:
[0122] a) from about 50 wt.% to about 70 wt.% of one or more polyphenols;
[0123] b) from about 15 wt.% to about 35 wt.% of one or more cationic polymers; and
[0124] c) from about 10 wt.% to about 30 wt.% of one or more ion transport enhancing proteins;
[0125] The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
[0126] Suitable polyphenols may be selected from polyphenols having a molecular weight of about 100 Daltons to about 20,000 Daltons or about 200 Daltons to about 20,000 Daltons.
[0127] Exemplary polyphenols may include one or more of the following: tannic acid, caffeic acid, gallic acid, ellagitannins, gallotannins, tannic acid, proanthocyanidins, and curcumin.Other polyphenols are contemplated.
[0128] Suitable cationic polymers may comprise amine functional groups. Exemplary cationic polymers may comprise one or more of the following: polyethyleneimine, poly(allylamine) hydrochloride, poly(lysine), poly(DADMAC), and chitosan. Other cationic polymers are contemplated.
[0129] Exemplary ion transport facilitating proteins include one or more of the following: bovine serum albumin, lysosome, ovalbumin, and valinomycin. Other ion transport facilitating proteins are contemplated.
[0130] The elastic polyelectrolyte fluid can be prepared by combining one or more polyphenols, one or more conductive polymers, and one or more ion transport facilitating proteins.
[0131] Preferably, the elastic polyelectrolyte solution can be prepared by first combining one or more polyphenols with one or more cationic polymers; and then adding one or more ion transport enhancing proteins.
[0132] Preferably, the elastic polyelectrolyte solution is prepared under acidic conditions.
[0133] Characteristics of elastic polyelectrolyte liquid
[0134] After combining one or more polyphenols, one or more cationic polymers, and one or more ion transport enhancing proteins, a dense phase and a transparent supernatant can be formed, and this mixture is conducive to self-assembly with one or more two-dimensional conductive materials.
[0135] In one embodiment, the polyphenol is tannic acid, the cationic polymer is polyethyleneimine, and the ion transport facilitating protein is bovine serum albumin. In one example, a suitable elastic polyelectrolyte liquid can be prepared by combining tannic acid, polyethyleneimine and bovine serum albumin in a weight ratio of about 60:25:15. The surface charge of such a composition as determined by zeta potential is about +40 mV. Fourier Transform Infrared spectroscopy indicates the presence of phenol, amine, carboxyl, carbonyl and amide stretching modes.
[0136] In another embodiment, the polyphenol is caffeic acid, the cationic polymer is polyethyleneimine, and the ion transport enhancing protein is bovine serum albumin. In one example, a suitable elastic polyelectrolyte solution can be prepared by combining caffeic acid, polyethyleneimine and bovine serum albumin in a weight ratio of about 60:15:25.
[0137] In another embodiment, the polyphenol is gallic acid, the cationic polymer is polyethyleneimine, and the ion transport enhancing protein is bovine serum albumin. In one example, a suitable elastic polyelectrolyte solution can be prepared by combining gallic acid, polyethyleneimine and bovine serum albumin in a weight ratio of about 60:15:25.
[0138] In another embodiment, the polyphenol is tannic acid, the cationic polymer is pDADMAC, and the ion transport enhancing protein is bovine serum albumin. In one example, a suitable elastic polyelectrolyte solution can be prepared by combining tannic acid, pDADMAC, and bovine serum albumin in a weight ratio of about 60:15:25.
[0139] In another embodiment, the polyphenol is tannic acid, the cationic polymer is polyethyleneimine, and the ion transport facilitating protein is lysosome. In one example, a suitable elastic polyelectrolyte solution can be prepared by combining tannic acid, polyethyleneimine and lysosome in a weight ratio of about 60:15:25.
[0140] Two-dimensional conductive materials
[0141] The one or more two-dimensional conducting materials may comprise one or more of: reduced graphene oxide, transition metal dichalcogenides, metal organic frameworks, phosphorene, and nitrides. Other two-dimensional conducting materials are contemplated.
[0142] Exemplary transition metal dichalcogenides may include MX 2 One or more of 2 、MoTe 2 and VS 2 , wherein M is Mo, W or V, and X is S, Se or Te.
[0143] Preparation of permselective sandwich
[0144] The permselective interlayer can be prepared by combining one or more elastic polyelectrolyte liquids with one or more two-dimensional conductive materials.
[0145] Preferably, the weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is about 1:1.5 to about 1:3.5.
[0146] In embodiments where the two-dimensional conductive material comprises graphene oxide, the mixture of one or more elastomeric polyelectrolyte liquids and one or more two-dimensional conductive materials is heated to a temperature greater than 60° C., preferably, to about 80° C., to convert at least some of the graphene oxide into reduced graphene oxide.
[0147] The heating may be performed for about 1 hour to about 36 hours, preferably about 8 hours to about 20 hours.
[0148] Characteristics of the permselective interlayer
[0149] The elastic polyelectrolyte liquid disclosed herein imparts advantageous properties to the selectively permeable interlayer when combined with a two-dimensional conductive material. The elastic polymer liquid improves ion transport and enhances coatability and adhesion to the diaphragm substrate. In addition, when the two-dimensional conductive material is graphene oxide, the elastic polyelectrolyte liquid reduces at least some of the graphene oxide in the graphene oxide to reduced graphene oxide.
[0150] In an embodiment, the selectively perminterlayer comprises both hydrophilic and hydrophobic domains.
[0151] In an embodiment, the zero shear viscosity of the permselective interlayer measured between 20°C and 25°C is less than 500 Pa.s.
[0152] In one embodiment in which the elastic polyelectrolyte liquid is formed of a mixture of tannic acid, polyethyleneimine and bovine serum albumin in a weight ratio of about 60:25:15, a suitable selective permeable interlayer can be produced by combining this mixture with graphene oxide in a weight ratio of about 1:2. After combination, gelation occurs, which may be caused by various interactions between the elastic polyelectrolyte liquid and the graphene oxide (such as π-π, hydrogen and Coulombic interactions). This is supported by the observation that after gelation, the zero shear viscosity of the graphene oxide and the elastic polyelectrolyte liquid, which is 45Pa.s and 4Pa.s, respectively, increases to 980Pa.s, and the surface charge of the material is +30mV. Heating to 80°C over a certain time range to reduce the graphene oxide produces a selective permeable interlayer with a zero shear viscosity of 250Pa.s and a surface charge of +37mV.
[0153] Diaphragm
[0154] Porous separators such as Celgard polyolefin separators are used in battery systems due to their inert nature and excellent stability. However, one drawback is their hydrophobic nature, which is not conducive to coating modification.
[0155] An advantageous feature of the presently disclosed permselective interlayer is that it can be cast on a hydrophobic surface such as Celgard surface due to the amphiphilicity of the polyphenol and ion transport promoting protein components and the excellent adhesion properties, i.e., due to the presence of both hydrophilic and hydrophobic domains in the interlayer.
[0156] Method for preparing diaphragm
[0157] A porous membrane substrate (such as Celgard) can be coated with the presently disclosed selectively permeable interlayer on one or both surfaces of the porous substrate.
[0158] The method for preparing the separator of the present disclosure is not particularly limited, and those skilled in the art may use known methods or various methods of modifying these methods.
[0159] In one method, the presently disclosed permselective interlayer is prepared and then coated on at least one surface of a porous substrate and then dried.
[0160] Useful porous separator substrates include polymers such as polyarylates, polyethylene terephthalate, polybutylene terephthalate, polysilanes, polysiloxanes, polysilazanes, polyethylene, polycarbosilanes, polyacrylates, poly(meth)acrylates, polymethyl acrylate, polymethyl (meth)acrylate, polyethyl acrylate, cycloolefin copolymers, polyethyl (meth)acrylate, cycloolefin polymers, polypropylene, polyimides, polystyrene, polyvinyl chloride, polyacetal, polyetheretherketone, polyester sulfone, polytetrafluoroethylene, polyvinylidene fluoride, perfluoroalkyl polymers, etc. Preferred porous substrates include polyolefins such as polyethylene or polypropylene.
[0161] The coating process can be controlled to provide a selectively permeable interlayer thickness of about 100 nm to about 400 nm, or about 150 nm to about 350 nm, or about 200 nm to about 300 nm on the porous substrate.
[0162] Diaphragm performance
[0163] The pore size of the permselective interlayer in a lithium-sulfur battery can advantageously be smaller than the pore size of lithium polysulfide (LiPS), but still allow Li + Sub-nanopores that block or hinder LiPS transport may + The significant mass transport resistance imposed by the transport of Li-S batteries has become a fundamental limitation of Li-S batteries. + Transport facilitates electrochemical reactions, and its obstruction may result in low active material utilization, concentration polarization, low CE, and high cell resistance.
[0164] Another limitation is that these hindered LiPS species may eventually accumulate on the interlayer surface, i.e., causing interlayer fouling and pore clogging. This may lead to active material loss, high microviscosity on the interlayer surface, surface passivation, and may create a feedback loop of deteriorated ion transport.
[0165] During cell operation, many different LiPS species are present in the electrolyte. + The ion concentration of salt is high [Li + ]≥1M, so the dominant species is the neutral ion triplet [Li 2 S n ] and its cluster [Li 2 S n ] x , while the lone ion pair [Li 2 S n ] - and [S n ] - Can be ignored. Among these many substances, Li 2 S 4is the most dominant species produced during operation, since Li 2 S 4 Reduction to Li 2 S accounts for about 75% of the theoretical battery cell capacity.
[0166] The permselective interlayer may be desirable to “reactivate” and “recycle” these accumulated LiPS species by promoting their conversion kinetics while mitigating the Li 2 Redox-mediated properties of irreversible deposition of S or electrocatalytic surfaces.
[0167] The currently disclosed permselective interlayer solves these problems. It is shown to be able to trap or block LiPS species transport while allowing Li ion transport, and also minimize the surface accumulation of the LiPS species by "reactivating" them due to the redox-mediated properties of the permselective interlayer.
[0168] In embodiments, the separators disclosed herein may block more than 90% of LiPS transfer across the separator, or reject more than 95% or up to 99% of LiPS transfer.
[0169] In embodiments, the separators disclosed herein oxidize and reduce LiPS on the surface of the selectively permeable interlayer, thereby reducing or eliminating the accumulation of LiPS on the surface.
[0170] Lithium-sulfur battery
[0171] The present disclosure provides a lithium-sulfur battery, which comprises a lithium anode, a sulfur cathode, a separator according to any one of the embodiments disclosed herein, and an electrolyte disposed between the anode and the cathode.
[0172] The selection of the lithium anode is not particularly limited. It can be lithium metal or a lithium alloy. Here, the lithium alloy contains an element that can be cast with lithium, and the element can be Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Co or an alloy thereof.
[0173] The choice of the sulfur cathode is not particularly limited. It may comprise elemental sulfur, a sulfur compound used in the art for constructing sulfur cathodes, or a mixture thereof.
[0174] The sulfur cathode may include a conductor. Commonly used conductors include graphite, carbon black, carbon fiber, carbon nanotubes, etc.
[0175] The sulfur cathode may further include a binder. However, the binder is not limited, and a binder typically used in the field of sulfur cathode construction may be used.
[0176] The electrolyte of the lithium-sulfur battery is an electrolyte solution containing a lithium salt, and may be an aqueous or non-aqueous electrolyte solution, and is preferably a non-aqueous electrolyte formed with an organic solvent electrolyte solution and a lithium salt. In addition, an organic solid electrolyte, an inorganic solid electrolyte, etc. may be used, however, the electrolyte solution is not limited thereto.
[0177] Examples of the non-aqueous organic solvent may include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxane, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate or ethyl propionate.
[0178] Lithium salts are materials that are favorably dissolved in non-aqueous electrolytes, and examples thereof may include LiCl, LiBr, LiI, LiNO 3 、LiClO 4 , LiBF 4 , LiB 10 Cl 10 、LiPF 6 、LiCF 3 SO 3 、LiCF 3 CO 2 、LiAsF 6 、LiSbF 6 、LiAlCl 4 , CH 3 SO 3 Li, CF 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 ,(CF 3 SO 2 ) 2 NLi, (FSO 2 ) 2 NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide, etc.
[0179] In an embodiment, the sulfur loading of the lithium-sulfur battery of the present disclosure is greater than 3 mg cm -2 or greater than 6 mg cm -2 .
[0180] In an embodiment, the electrolyte volume to capacity ratio of the lithium-sulfur battery of the present disclosure is less than or equal to 5 μL mAh -1 .
[0181] Lithium-sulfur battery performance
[0182] The coin cell battery including the separator disclosed herein has a capacity of 4.9-5.3 μL mAh. -1 The results show that the 4.8-8.1 mAh cm-2 capacity can be stably achieved over 450 cycles at a very low electrolyte / capacity (E / C) ratio. -2 area capacity.
[0183] A pouch cell prototype (3 cm×5 cm) including the separator disclosed herein achieved an energy density of 202 Wh kg-1 over 100 stable cycles.
[0184] Examples
[0185] Material
[0186] The sulfur cathode contained crystalline sulfur (Sigma Aldrich), carbon (Black Pearls 2000, CABOT Co.) and carboxymethyl cellulose binder (Sigma). The elastic polyelectrolyte liquid (EPL) contained tannic acid (Sigma), polyethyleneimine (Mn1000, Sigma) and bovine serum albumin (heat shock fraction, Sigma). Graphene oxide paste (The Sixth Element Inc.) was purified and exfoliated and made into a suspension by adding deionized water. Lithium bis(trifluoromethane)sulfonyl imide salt and lithium nitrate were purchased from Sigma Aldrich and used directly without any further purification. Dimethoxyethane (DME) and 1,3-dioxolane (DOL) solvents were purchased from Sigma. Li was purchased from Alfa Aesar. 2 S for lithium polysulfide synthesis. Battery grade etched Al foil was purchased from Japan Capacitor Industrial Co., and Celgard 2730 was purchased from Celgard Inc., USA.
[0187] Example 1: Preparation of elastic polyelectrolyte liquid (EPL)
[0188] The elastic polyelectrolyte liquid (EPL) was synthesized by combining the components in different ratios. The tannic acid (TA) solution was vigorously stirred at 1000 rpm and then heated at 1 mL min-1 Polyethyleneimine (PEI) was added at a rate of 1:1, followed by bovine serum albumin (BSA) until the desired ratio was achieved. All EPL samples were prepared at pH 5 to prevent or minimize any covalent reactions (such as Michael addition reactions) that may occur under alkaline conditions.
[0189] The variation in the TA:PEI:BSA ratio indicates the component ratio in which the preferred EPL is formed. Figure 1 The ratios of the TA:PEI:BSA system are shown, highlighting the regions where EPL is preferred.
[0190] The amphiphilicity of EPL was demonstrated by its ability to produce a stable oil-in-water emulsion with paraffin oil and water (30 vol% oil). This suggests that the hydrophobic domains of EPL are able to interact with paraffin oil, while the hydrophilic domains of EPL interact with water to produce an otherwise immiscible stable solution.
[0191] Example 2: Preparation of a sandwich comprising EPL and reduced graphene oxide
[0192] EPL was added to a suspension of graphene oxide (GO) at a given mass ratio and stirred vigorously. Gelation was observed after 15 minutes. For all EPL-GO mixtures, stirring was performed overnight. For reduction, the EPL-GO suspension was then heated to 80 ° C for different times to produce elastic polyelectrolyte liquid reduced graphene oxide (EPL-rGO) for subsequent use as an interlayer.
[0193] Example 3: Changing the amount of interlayer components
[0194] Several EPL-rGO interlayer samples were prepared with different component amounts. The details are collected in Table 1, and the samples are ranked according to several performance parameters. Each EPL composition was mixed with graphene oxide in a weight ratio of 1:2 (EPL:GO) and reduced at 70°C for 12 hours. The relative sheet resistance was used as a proxy for the degree of reduction of the oxidized GO. The amphiphilicity was estimated by the coatability of the material on bare Celgard, as a measure of the extent to which it can be used to coat the hydrophobic surface of Celgard. Its selective permeability was evaluated by diffusion cell testing. The ionic conductivity was measured by electrochemical impedance spectroscopy (EIS).
[0195]
[0196] The results show that: i) the reduction of GO can be mainly attributed to TA, but also to PEI; ii) all components may contribute to the improvement of ion transport, most notably BSA improves ion transport, and then there is a diminishing return beyond a certain fraction; iii) Li + Affinity can be correlated with PEI content; iv) favorable adhesion properties can originate from BSA and TA; v) permselectivity can be attributed to BSA content. These results are further discussed in the following paragraphs.
[0197] Example 4: Characterization of EPL-rGO interlayer
[0198] Figure 2 F is a bright field polarized microscopy image of EPL-rGO (60:25:15 EPL composition) of Example 3, showing liquid crystalline domains. This indicates that even after reduction, a high degree of structural order is retained. Figure 2 E shows the change in viscosity of EPL, GO, the combination of EPL and GO, and EPL-rGO. It can be seen that after the combination of EPL and GO, the zero shear viscosity increases significantly, which is consistent with the observed gelation. After reduction, the zero shear viscosity decreases.
[0199] The reduction of EPL-GO to EPL-rGO was further demonstrated by the increase in electrical conductivity with respect to reduction time (see Figure 3 ). It can be seen that long reduction times may have a negative impact on the coatability of EPL-rGO. Excessive reduction may lead to the formation of particulate material, which may reduce the performance as an interlayer material. The reduction is further supported by Fourier transform infrared (FTIR) spectroscopy, which shows a decrease in the intensity of peaks associated with CO and C=O bonds, and X-ray spectroscopy (XPS), which shows a decrease in the relative intensity of sp2 domains to sp3 domains, indicating that deoxygenation of GO has occurred. Raman spectroscopy studies show that the G band in the spectrum shifts to lower frequencies (red shift) from EPL-GO to EPL-rGO, which further supports the reduction.
[0200] As demonstrated by its stability, EPL-rGO also maintains long-term colloidal stability even after 3 months of storage at room temperature.
[0201] Example 5: Diaphragm Preparation
[0202] EPL-GO, EPL-rGO, and rGO were coated on Celgard. However, in order to compare between the permselective interlayers, Celgard was dip-coated on 15 g L -1The coating of Celgard was improved by tannic acid solution for 15 minutes, thereby rendering it hydrophilic, and this hydrophilized Celgard was used for all experiments. Coating was performed by rod coating. The rGO interlayer was reduced by UVC light (254 nm). The exposure time was tuned to obtain a sheet resistance similar to that of EPL-rGO in about 220 minutes.
[0203] Example 6: Study on EPL-rGO interlayer
[0204] The cutoff value of molecular rejection of LiPS is about By tuning the reduction degree and the ratio of EPL to GO, the interlayer spacing can be manipulated to meet this design criterion. For EPL-rGO, X-ray diffraction (XRD) shows two peaks, indicating the presence of a dual channel spacing, where the broad channel is And the narrow channel is ( Figure 4 B) It should be noted that when EPL-rGO is immersed in solvent for 24 h, the difference between the wet and dry spectra is small, indicating that the change in the interlayer spacing is negligible. The narrow channels are composed of domains of highly reduced and stacked sheets, i.e., the stacking of sheets between the graphitic regions is sp 2 The broad channels are the result of EPL embedding into the sheets. This is schematically depicted in Figure 4 A. Positron annihilation lifetime spectroscopy (PALS) analysis revealed that, according to Figure 4 The spectrum in C, the average interlayer spacing is This means that about 15% of the channels are narrow and about 85% of the channels are wide. Both narrow and wide channels repel LiPS, but the wider channels allow Li + Increased penetration.
[0205] Example 7: Repellency of interlayer
[0206] The repellency properties of the interlayer were investigated in a diffuse cell with Li dissolved in DOL / DME on one side of the cell. 2 S 4 and on the other side has DOL / DME, such as Figure 5 Shown in A. Li 2 S 6 With Li 2 S 4 The solution was synthesized following the method reported in Liao et al., Journal of Materials Chemistry (J. Mater. Chem.), Vol. 4, pp. 5406-5409, 2016. Elemental sulfur and Li 2S powder was mixed in a solvent of DOL and DME (DOL / DME=50 / 50 (v / v)) at an appropriate molar ratio under stirring in an argon glove box at 50° C. for 48 hours. The resulting solution was centrifuged at 5000 rpm for 10 minutes, and any unreacted particles were removed.
[0207] The Li 2 S 4 The quantification performed showed that the EPL-rGO interlayer was able to reject 99% of Li2S4, while GO and rGO interlayers achieved 32% and 91%, respectively, and the rejection rate of EPL-GO was 79%. Figure 5 A visual summary of the results is provided in B.
[0208] The repellency depends not only on the interlayer spacing but also on the stability in harsh electrolyte and LiPS environments, e.g. Figure 5 As shown in C. The interlayer coated on Celgard was in the presence of LiTFSI and LiNO 3 The case was immersed in 2mMLi 2 S 6 The GO coating lost its structural integrity under the solvated conditions. The rGO coating showed poor conformational stability and the separator curled up after 48 hours. Although EPL-GO showed improvement in maintaining anchoring to the underlying substrate, its interlayer spacing was This is slightly above the threshold for LiPS repulsion. The strong interaction between EPL and rGO and the strong interlayer interaction between the narrow channels (i.e., sp 2 Strong π-π stacking between domains is important for maintaining structural integrity and mitigating solvent swelling.
[0209] The thickness of the EPL-rGO interlayer coated on Celgard varied between 70 nm and 480 nm. Figure 6 is a plot of interlayer thickness versus ionic conductivity and lithium polysulfide rejection. Higher interlayer thicknesses yield higher polysulfide rejection, however ionic conductivity is negatively impacted. An interlayer thickness of approximately 250 nm produces a useful balance between the ability to reject LiPS while maximizing ionic conductivity.
[0210] By placing the desired separator on one side with 0.3M Li 2 S 4 The diffusion cell study was performed by placing a blank solvent between the two chambers of the diffusion cell on one side and allowing permeation for 48 hours. The polysulfide rejection value was calculated as
[0211]
[0212] Among them C b is the concentration on the blank side at time t (48 hours), and C i is the initial concentration on the LiPS side. To test the stability of different separators, they were immersed in a solution with LiTFSI and LiNO 3 0.05M Li 2 S 4 The diffusion cell test was set up with electrolyte on one side and blank solvent on the other side. + Diffusion flux. The diffusion flux D is calculated by Li + :
[0213]
[0214] Where n t is the impregnation Li in mmol after 24 hours + Passing through effective area A(m 2 ) of the diaphragm for a total time t (hours).
[0215] Example 8: Battery Fabrication and Electrochemical Characterization
[0216] The cathode consisted of 70 wt% sulfur, 20 wt% carbon black and 10 wt% CMC binder, which was made into a thick aqueous slurry and tape cast on an Al foil current collector using a doctor blade. The cathode was air dried for 2 hours and further dried in a vacuum oven at 50 °C overnight. The cathode was then cut into 1 cm 2 The disk was heated in an Ar-filled glove box under O 2 CR2032 coin cell cells were assembled using Li metal anodes, the aforementioned cathodes, and separators with different permselective interlayer coatings at 37 °C and humidity <0.1 ppm. For electrochemical characterization, a Neware battery cycler (Neware Technology Limited) was used at 27 °C relative to Li / Li + A galvanostatic charge and discharge method (same charge / discharge current) was applied in the voltage range of 1.8-2.7 V. The ion exchange rate was measured on an EC-Lab (BioLogic Science Instruments, France) at different scan rates and relative to Li / Li +Cyclic voltammetry (CV) was performed in the voltage range of 1.8-2.8 V. Electrochemical impedance spectroscopy (EIS) was also performed using EC-Lab to measure the response in frequencies between 1 MHz and 10 mHz, with six points recorded per decade of frequency. Impedance was repeated three times to ensure reproducibility. according to The diffusion coefficient was calculated by the equation, where the measured current of different CV curves showed a power law relationship with the scan rate:
[0217]
[0218] Among them I p is the peak current (A), n is the number of electrons in the redox reaction (n = 2), and A is the electrode area (cm 2 ), It's Li + Diffusion coefficient (cm 2 s -1 ), C Li is Li in the electrolyte + Concentration (mol mL -1 ), and the scan rate is v(V s -1 ). By using 3 mg cm on both sides of Al substrate -2 The load is made of 3.3×5.3cm 2 The cathode was used to prepare the pouch cell. The lithium anode (foil, 0.1 mm thickness) was cut into 3.5×5.5 cm 2 The EPL-rGO coated separator was placed between the two electrodes with the EPL-rGO facing the cathode. Electrolyte was added to satisfy the condition E / S ratio = 5. Cycling performance was performed using BT-Lab and EIS was performed using EC-Lab. The gravimetric energy density was calculated according to the following equation:
[0219]
[0220] Where V is the average battery cell voltage, which is 2.1V, m a is the mass of active material, C s is the specific capacity, and Σm i is the sum of the masses of all components including cathode, anode, separator and electrolyte. The calculated energy density is consistent with the value reported on the BT-Lab software.
[0221] Example 9: Button Cell Battery Performance
[0222] A standard cathode was employed, which contained sulfur, a conductive carbon additive, and a water-soluble binder and was used consistently throughout the study.-2 The cycling performance of different separators with the same interlayer coating thickness and E / S ratio was compared at a sulfur loading of 2.5 % and a cycling rate of 0.1 C (see Figure 7 A) EPL-rGO interlayer showed that at 1,505 mAh g -1 The maximum capacity (90% sulfur utilization) and CE>99% after 120 cycles with minimal capacity decay. In contrast, the capacity of EPL-GO is significantly lower at 1,102 mAh g -1 , and experienced 80 stable cycles before rapid capacity decay set in. The battery cells using EPL-rGO were able to -1 ) maintains excellent cycling stability without capacity loss. The bare GO interlayer has a very low initial capacity and limited cycle life.
[0223] Electrochemical characterizations including cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge-discharge curve analysis were performed to further investigate the performance differences.
[0224] CV is used to gain insight into the electrochemical processes occurring between the anodic and cathodic processes and allows comparison of reaction kinetics. Figure 7 B shows that the EPL-rGO interlayer has anodic peaks at 2.41 V and 2.33 V, and cathodic peaks at 2.37 V and 2.06 V. Compared with other interlayers, its peaks are sharper and show higher peak current density, where the cathode reaction potential is significantly higher and the anodic potential is lower. The peak position and high current density indicate that the EPL-rGO interlayer has excellent ion transport properties, accelerates the redox kinetics of lithium polysulfide (LiPS) reactions, and can effectively inhibit LiPS shuttling.
[0225] Figure 7 The galvanostatic charge-discharge curves in D complement the CV data. The voltage range of the plateau and its corresponding capacity are determined by the Li + The second plateau appears at 2.05 V and 380 mAh g for the EPL-rGO interlayer. -1 This indicates that the cathode Li + The availability of higher order LiPSs and the fast ion transport and rapid redox reactions of LiPSs are the main contributing factors to the capacity. The length of the second plateau extends to 950 mAh g -1 , indicating excellent LiPS retention and catalytic conversion of lower-order LiPS to Li 2 S ability to respond.
[0226] The significantly larger potential barriers of GO interlayer, rGO interlayer and EPL-GO interlayer in the initial stage of the charging process reveal that a high overpotential is required to convert the insulating Li 2 The S discharge products are converted to LiPS, and the absence of redox-mediated properties results in delayed diffusion kinetics. In addition, the significantly lower polarization when EPL-rGO is used as an interlayer further indicates the combined effects of shuttle suppression, excellent ion transport, and a significant ability to enhance LiPS conversion reactions. The higher polarization of the other interlayers may be a combination of poor ion transport and concentration polarization of LiPS on their surfaces. As a result of ohmic polarization and concentration polarization, the internal resistance (IR) drop of each interlayer at the beginning of the discharge spectrum is significantly lower than the IR drop of the EPL-rGO interlayer.
[0227] Electrochemical impedance spectroscopy (EIS) was used to further investigate the kinetics of ion transport and LiPS regulation by comparing internal cell resistances. Figure 7 C. The figure consists of a semicircle in the high frequency region and a slant line (Warburg impedance) in the low frequency domain, the diameter of which can be assigned as the charge transfer resistance, which is related to the capacity decay and electrochemical response. The EIS results complement the findings of the CV curve and the charge-discharge curve. The reduction in the internal resistance of EPL-rGO may be due to its favorable ion transport architecture, lithium affinity, and its ability to act as both the above current collector and redox mediator to promote the LiPS conversion reaction due to its conductivity.
[0228] At a high cycling rate of 0.4C, a maximum capacity of 1,382 mAh g-1 was achieved after several activation cycles, which exhibited a CE greater than 98.5% at approximately 450 stable cycles, as shown in Figure 2. Figure 7 As shown in E. At 6 mg cm -2 At a relatively high sulfur loading of 1.5 mAh cm-2, an areal capacity of >7 mAh cm-2 was maintained for 70 cycles at a rate of 0.1 C (at 8.1 mAh cm-2). -2 The capacity loss is minimized at an extremely low electrolyte to capacity (E / C) ratio of 4.9 μL mAh-1. Figure 7 F).
[0229] Electrochemical impedance spectroscopy (EIS) studies showed that the internal cell resistance increased with the number of cycles, indicating high reversibility of the battery, with little increase observed after 300 cycles. CVs were performed at four different scan rates, which exhibited a strong current response and showed excellent reaction kinetics. The measured current showed a power law relationship with the scan rate, according to The power law relationship is related to the Li+ diffusion coefficient D_Li^+. The D_Li^+ of the entire battery cell is about 10 -9 cm 2 s -1 .
[0230] Example 10: Pouch Cell
[0231] Using EPL-rGO membrane, double-sided sulfur cathode (single-sided sulfur loading of 3 mg cm -2 , total 6 mg cm -2 ) and a 100 μm thick lithium metal anode with an E / S ratio of 5. After 100 cycles at a rate of 0.05C, the delivered initial energy density was 202 Wh kg-1 and the capacity was 925 mAh g-1. The cycling data are presented in Figure 8 A.
[0232] Figure 8 The charge-discharge spectra in C show that the second plateau starts at 2.08 V and 290 mAh g-1, which indicates low polarization and decreases under IR. The high voltage of the second plateau is essential for the energy density. Figure 8 The Nyquist plot in D shows that the impedance spectrum exhibits negligible changes, even after 40 cycles.
[0233] Example 11: Lithium ion transport study
[0234] Fig. 9 A shows the battery cell configuration used to measure ionic conductivity and Li+ transfer number. Fig. 9 B shows the results for different interlayers and also shows images of the electrolyte contact angles for different interlayers.
[0235] Fast Li + Ion transport is essential for Li + It is important to make the ions more readily available at the cathode and enable them to react with sulfur during discharge (and vice versa during charge), thereby improving sulfur utilization, CE, and cycle life. In electrochemical devices, the ion transport of the separator is characterized by: ionic conductivity (σ m ), wherein the ionic conductivity includes a diffusion driving force and a potential driving force; and Li + Transfer number (t Li + ), which describes Li + and its co-ions (such as TFSI - and NO 3 - ) The total current carried by the two + The ion current carried.
[0236] Due to Li + The radius of the solvation is significantly larger than the pore size required to exclude LiPS, so i) the first step is Li + must undergo desolvation and splitting of the ion pairs at the interlayer surface; ii) then, Li + The ion must be "adsorbed" and "stabilized" to partition into the pores; iii) this is followed by diffusion through the interlayer, which can be interpreted as a series of formation, breaking and reformation of bonds with the next coordinating atoms. Fig. 9 The schematic in C outlines the proposed mechanism.
[0237] according to Fig. 9 Slope calculation Li in D + The activation energy required to transport through the interlayer. The activation energy of Celgard at 95% confidence level is 32.1 ± 0.39 kJ mol -1 , while for GO, the activation energy is 33.2±0.23 kJ mol -1 After adding EPL, the activation energy for EPL-GO increased to 27.3 ± 0.50 kJ mol -1 , and for EPL-rGO, the value is similar, 26.9 ± 0.42 kJ mol -1 .
[0238] Example 12: Electrocatalytic Activity of Diaphragm
[0239] In order to confirm the redox-mediated properties of EPL-rGO, different interlayers were used to face the bottom shell current collector using 0.5 M Li 2 S 6 The electrolyte (catholyte) and Li anode are assembled into a coin cell. The setup is shown in Fig.10 A. Fig.10 The CV scans at three different scan rates in B show two cathodic peaks, which are related to the conversion of high-order LiPS to short-chain LiPS and then to the final discharge product Li 2 The strong and sharp peak intensity in the presence of EPL-rGO material alone (in the absence of sulfur or conductive carbon additives) greatly confirms its excellent catalytic activity and kinetics of LiPS conversion.
[0240] Complementary experiments to establish the electrocatalytic activity towards LiPS were performed in symmetric cell experiments. Symmetric cells were assembled with identical working and counter electrodes in 0.5 M cathode electrolyte. The cells were charged at 10 mV s between -0.8 V and 0.8 V. -1 The scan rate cycle, which is shown in Fig.11 The current response of EPL-rGO is the highest, which is consistent with the concept that redox-mediated interlayer plays a major role in enhancing the redox kinetics of LiPS and is consistent with the results observed from the cathode electrolyte cell. The peaks at +0.35 V and -0.42 V are related to Li 2 S 6 The reduction and oxidation on the interlayer surface are consistent. These results are in sharp contrast to the other interlayers. GO and EPL-GO show negligible peaks due to lack of conductivity, while rGO shows broad anodic and cathodic peaks and a current density of about 1 / 20 of that of the GO and EPL-GO due to lack of interaction and low affinity with LiPS.
[0241] exist Fig.12 Comparisons were made with commonly used redox mediator materials in Li-S cells, maintaining the same mass ratio of LiPS to redox mediator materials for a fair comparison. Without the addition of conductivity additives, the EPL-rGO interlayers outperformed the well-known electrocatalytic materials, producing sharper peaks and higher current densities. Only with the addition of conductive carbon were the CV curves comparable. The notable exceptions are that, unlike EPL-rGO, these coatings are not permselective, have lower LiPS adsorption capacities than that of EPL-rGO, and require considerably higher electrolyte volumes for complete wetting.
[0242] Example 13: Preparation and Use of Additional Elastomeric Polyelectrolyte Liquids (EPLs)
[0243] Additional elastomeric polyelectrolyte liquids (EPLs) were prepared as described in Example 1 using various polyphenols, cationic polymers, and ion transport enhancing proteins and at a mass ratio of 60:15:25. The formulations are shown in Table 2.
[0244]
[0245] Interlayer materials comprising EPL formulations 1 to 4 of Table 2 and graphene oxide (GO) at an EPL:GO ratio of 1:2 were prepared as in Example 2. Reduction was performed at 70°C for 12 hours and the corresponding EPL-rGO formulations were coated onto Celgard substrates as in Example 5. Adhesion to the substrate and film quality were observed to be of very good quality.
[0246] As in Example 9, 3 mg cm -2 Button battery cells were prepared with sulfur loading of 100 μg / mL and the cycling performance of different separators at a cycling rate of 0.25 C was compared.
[0247] Fig.13It is shown that four formulations (1, 2, 3 and 4) showed minimal capacity decay after 150 cycles.
[0248] Electrochemical characterization
[0249] The ionic conductivity of the separator was calculated by EIS and repeated three times. Each separator was saturated with electrolyte (20 μL) and sandwiched between two stainless steel electrodes of a button cell. It was allowed to stand for 12 hours and the ionic conductivity was calculated according to the following equation:
[0250]
[0251] where σ is the ionic conductivity, L is the thickness of the interlayer, A is the area of the stainless steel electrode, and R b is the volume resistance. Li is calculated by the Bruce-Vincent method through a combination of AC impedance measurement and DC polarization + Transfer number. The electrolyte-soaked separator (20 μL) was placed between the two Li electrodes of the coin cell. The Li + Number of transfers
[0252]
[0253] where ΔV is the potential difference applied by chronoamperometric step, which is 10 mV, and I SS and I 0 is the steady-state and initial current, while R SS and R 0 is the steady-state and initial interfacial resistance determined by impedance spectroscopy. The activation energy is calculated based on the Arrhenius relation for a symmetric cell. Keeping all other constants, the activation energy E a Allow based on Li + The desolvation energy of is compared with the diffusion through the membrane. The Arrhenius relation is given by:
[0254]
[0255] Where A is the prefactor, R ct is the impedance (ohm), T is the temperature (K), and R is the gas constant (J mol -1 K -1 ).
[0256] Diaphragm Characterization
[0257] Static electrolyte contact angle measurements were performed on the diaphragm using a Dataphysics OCA35 contact angle instrument at room temperature and 50% controlled humidity using a sessile drop method, and the drop volume was 6 μL. The electrolyte absorption of the diaphragm was determined by soaking the electrolyte solution for 2 hours, and the weight of the diaphragm was extracted after removing excess electrolyte from the surface using filter paper. The test was performed in a glove box under an inert argon atmosphere. The electrolyte absorption was calculated using the following equation:
[0258]
[0259] The filtration was carried out in a dead-end filtration cell from Sterlitech (HP4750 stirred cell, Sterlitech USA) at a temperature of 14.6 cm 2 The effective surface area of the membrane was subjected to solvent penetration to test the hydrodynamic permeability of different membranes. The pressure was maintained at 200 mbar, and the mass and pressure were recorded every second using a Radwag precision balance (PS1000.R2, Poland) and a Fluigent pressure pump (MFCS-EX, France). The membrane was allowed to stabilize for 2 hours to obtain the penetration results, and repeated three times to ensure reproducibility. The penetration J is defined as:
[0260]
[0261] Where V p is the volume that permeates through the effective area A and the applied pressure P at time t.
[0262] Additional Characterization Techniques
[0263] An attenuated total reflectance FTIR spectrometer (PerkinElmer, USA) was used at 400–4000 cm -1 The range is 2cm in an average of 32 scans. -1 Fourier transform infrared spectroscopy (FTIR) spectra were recorded at a resolution of 1.3 Å. X-ray photoelectron spectroscopy (XPS) was performed to determine the sp 2 Peak and sp 3Peaks were used to study the reduction of EPL-rGO. The spectroscopy was performed using a Nexsa surface analysis system (ThermoFisher Scientific, USA) using a monochromatic Al Kα source. Scanning electron microscopy (SEM, FEI Nova NanoSEM 450FEG) was used to study the morphology of the nanoparticle images. The samples were mounted on Al piles and coated with iridium using a Cressington 208HRD sputtering instrument to a thickness of about 2 nm. Secondary electron images were collected at an accelerating voltage of 5 kV and a working distance of 5 mm. UV-Vis was used to determine the lithium polysulfide concentration by first preparing a set of standards to make a calibration curve (Lambda 365, PerkinElmer, USA). At 0.4°min -1 The X-ray diffraction (XRD) analysis using Bruker D2Phaser diffractometer with Cu Kα radiation was produced at 30 kV and 10 mA at a scan rate of 0.02 ° and a step size of 0.02 °. Raman spectra were obtained using a Renishaw Confocal micro-Raman Spectrometer (Renishaw Confocal micro-Raman Spectrometer) equipped with a HeNe (632.8 nm) laser instrument operated at 10% power. Extended scanning (10 seconds) was performed with a laser spot size of 1 μm between 100 wave numbers and 3200 wave numbers. After background removal, the intensity of the spectrum was normalized by dividing the data by the maximum intensity. Surface charge was evaluated using a dynamic light scattering analyzer (NanoBrook 90Plus PALS, Brookhaven, USA). Rheological tests were performed using a strain-controlled AREAS G2 rheometer (TA instruments, USA) with a cone-plate geometry (cone angle 2° and cone diameter 50 mm). During the test, a constant gap of 0.045 mm was maintained. The temperature was controlled at 23.00 ± 0.01 °C for the experiments. For steady-state measurements, a 0.01 s -1 -100s -1 The shear rate range is 2000 s. Polarized light microscopy was performed using an inverted Leica DM IRB microscope equipped with an Abrio polarized light imaging system from CRI Inc., and images were extracted in a birefringence setting mode that included a linear polarizer, an analyzer, and two variable electro-optical delay plates instead of a compensator. Polarized light was transmitted through a sample loaded in a clean microscope slide, passed through an analyzer, and captured by a CCD camera. The captured signals were processed in turn using a digital image processing system to generate light delay and slow axis orientation images.
Claims
1. A permselective interlayer for a lithium-sulfur battery, the permselective interlayer comprising: a) one or more elastomeric polyelectrolyte liquids; and b) One or more two-dimensional conducting materials.
2. The selectively permeable interlayer of claim 1, wherein the interlayer comprises: a) from about 15 wt.% to about 45 wt.% of one or more elastomeric polyelectrolyte liquids; and b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials; The wt. % is based on the total weight of the permselective interlayer.
3. The selectively permeable interlayer of claim 2, wherein the interlayer comprises: a) from about 20 wt.% to about 40 wt.% of one or more elastomeric polyelectrolyte liquids; and b) from about 40 wt.% to about 80 wt.% of one or more two-dimensional conductive materials; The wt. % is based on the total weight of the permselective interlayer.
4. The selectively perminterlayer according to any one of claims 1 to 3, wherein the weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is from about 1:1.5 to about 1:3.
5.
5. The permselective interlayer according to any one of claims 1 to 4, wherein the elastic polyelectrolyte liquid comprises a mixture of: a) from about 50 wt.% to about 80 wt.% of one or more polyphenols; b) from about 5 wt.% to about 40 wt.% of one or more cationic polymers; and c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins; The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
6. The permselective interlayer according to any one of claims 1 to 5, wherein the elastic polyelectrolyte liquid comprises a mixture of: a) from about 50 wt.% to about 80 wt.% of one or more polyphenols; b) from about 15 wt.% to about 40 wt.% of one or more cationic polymers; and c) from about 5 wt.% to about 35 wt.% of one or more ion transport enhancing proteins; The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
7. The permselective interlayer according to any one of claims 1 to 6, wherein the elastic polyelectrolyte liquid comprises a mixture of: a) from about 50 wt.% to about 70 wt.% of one or more polyphenols; b) from about 15 wt.% to about 35 wt.% of one or more cationic polymers; and c) from about 10 wt.% to about 30 wt.% of one or more ion transport enhancing proteins; The wt. % is based on the total weight of the elastic polyelectrolyte liquid.
8. The permselective interlayer of claim 6 or claim 7, wherein the one or more polyphenols have a molecular weight of about 100 Daltons to about 20,000 Daltons.
9. The selectively permeable interlayer of any one of claims 6 to 8, wherein the one or more polyphenols comprise one or more of the following: tannic acid, caffeic acid, gallic acid, ellagitannin, gallotannin, tannic acid, proanthocyanidin, and curcumin.
10. The permselective interlayer of any one of claims 6 to 9, wherein the one or more cationic polymers comprise amine functional groups.
11. The permselective interlayer of any one of claims 6 to 9, wherein the one or more cationic polymers comprise one or more of: polyethyleneimine, poly(allylamine) hydrochloride, poly(lysine), poly(DADMAC), and chitosan.
12. The permselective interlayer according to any one of claims 6 to 11, wherein the one or more ion transport enhancing proteins comprise one or more of the following: bovine serum albumin, lysosome, ovalbumin, and valinomycin.
13. The selectively permeable interlayer according to any one of claims 1 to 12, wherein the one or more two-dimensional conductive materials comprise one or more of the following: reduced graphene oxide, transition metal dichalcogenides, metal organic frameworks, phosphorene, and nitrides.
14. The selectively permeable interlayer of claim 13, wherein the transition metal dichalcogenide comprises one or more of MX2, wherein M is Mo, W or V, and X is S, Se or Te.
15. The selectively perminterlayer according to any one of claims 1 to 14, wherein the interlayer comprises both hydrophilic and hydrophobic domains.
16. The permselective interlayer according to any one of claims 1 to 15, wherein the interlayer has a zero shear viscosity of less than 500 Pa.s measured between 20°C and 25°C.
17. A separator for a lithium-sulfur battery, the separator comprising a porous substrate coated with a selectively permeable interlayer according to any one of claims 1 to 16.
18. The membrane of claim 17, wherein the selectively permeable interlayer coating comprises pores of a size large enough to allow transport of lithium ions through the membrane.
19. The membrane of claim 17 or claim 18, wherein the selectively permeable interlayer coating comprises pores of a size sufficiently small to impede transport of polysulfide species through the membrane.
20. The membrane of any one of claims 17 to 19, wherein the permselective interlayer coating mitigates accumulation of polysulfide species on a surface of the permselective interlayer coating.
21. The membrane of any one of claims 17 to 20, wherein the porous substrate comprises one or more polyolefins.
22. The membrane of any one of claims 17 to 21, wherein the selectively permeable interlayer coating has a thickness of about 100 nm to about 400 nm, or about 150 nm to about 350 nm, or about 200 nm to about 300 nm.
23. A lithium-sulfur battery comprising a lithium anode, a sulfur cathode, a separator coated with a selectively permeable interlayer according to any one of claims 1 to 16, and an electrolyte disposed between the anode and the cathode.
24. The lithium-sulfur battery of claim 23, wherein the permselective interlayer coating mitigates accumulation of polysulfide species on a surface of the permselective interlayer coating during charge or discharge.
25. The lithium-sulfur battery of claim 24, wherein the permselective interlayer coating oxidizes and reduces polysulfide species during charge and discharge.
26. The lithium-sulfur battery of any one of claims 23 to 25, wherein the permselective interlayer coating facilitates transport of lithium ions across the separator during charge or discharge.
27. The lithium sulfur battery of any one of claims 23 to 26, wherein the permselective interlayer coating impedes transport of polysulfide species through the separator during charge or discharge.
28. The lithium-sulfur battery of claim 27, wherein the permselective interlayer coating blocks transport of more than 90% of polysulfide species, or more than 95%, or up to 99% or more of polysulfide species through the separator.
29. The lithium-sulfur battery according to any one of claims 23 to 28, wherein the electrolyte volume to capacity ratio is less than or equal to 5 μL mAh -1 .
30. A method of producing a permselective interlayer according to any one of claims 1 to 16, the method comprising combining one or more elastic polyelectrolyte liquids with one or more two-dimensional conductive materials.
31. The method of claim 30, wherein the two-dimensional conductive material is graphene oxide.
32. The method of claim 31, wherein the combination of one or more elastomeric polyelectrolyte liquids and graphene oxide is heated to a temperature greater than 60°C to reduce at least some of the graphene oxide.
33. The method of any one of claims 30 to 32, wherein the weight ratio of the one or more elastic polyelectrolyte liquids to the one or more two-dimensional conductive materials is from about 1:1.5 to about 1:3.
5.
34. A method of producing a membrane according to any one of claims 17 to 22, the method comprising coating a porous substrate with a selectively permeable interlayer according to any one of claims 1 to 16.
35. An elastic polyelectrolyte solution comprising a mixture of one or more polyphenols, one or more cationic polymers and one or more ion transport enhancing proteins.
36. A method for preparing the elastic polyelectrolyte solution according to claim 35, the method comprising: a) combining one or more polyphenols with one or more cationic polymers; and b) adding one or more ion transport enhancing proteins, Wherein a) and b) are carried out under acidic conditions.